2021
DOI: 10.3847/1538-4357/ac23c7
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Wave Properties in Footpoints of Coronal Loops in 3D MHD Simulations

Abstract: Acoustic waves excited in the photosphere and below might play an integral part in the heating of the solar chromosphere and corona. However, it is yet not fully clear how much of the initially acoustic wave flux reaches the corona and in what form. We investigate the wave propagation, damping, transmission, and conversion in the lower layers of the solar atmosphere using 3D numerical MHD simulations. A model of a gravitationally stratified expanding straight coronal loop, stretching from photosphere to photos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…Following the initial setup for the simulations of Riedl et al (2021), we use the same coronal loop model of Reale et al (2016) featuring a straightened, evacuated loop spanning from photosphere to photosphere in a cylindrical coordinate system. The initial equilibrium is obtained by numerically relaxing a hydrostatic model over time, featuring a photosphere, transition region (TR), and corona, with vertical and straight magnetic field (Guarrasi et al 2014).…”
Section: Modelmentioning
confidence: 99%
“…Following the initial setup for the simulations of Riedl et al (2021), we use the same coronal loop model of Reale et al (2016) featuring a straightened, evacuated loop spanning from photosphere to photosphere in a cylindrical coordinate system. The initial equilibrium is obtained by numerically relaxing a hydrostatic model over time, featuring a photosphere, transition region (TR), and corona, with vertical and straight magnetic field (Guarrasi et al 2014).…”
Section: Modelmentioning
confidence: 99%
“…It was found that these modes couple efficiently to Alfvén waves through resonant absorption (Hansen & Cally 2009;Cally & Andries 2010;Khomenko & Cally 2012). Currently, investigations into what happens if the cross-field structuring is included in the wave propagation model are ongoing (Cally & Khomenko 2019;Riedl et al 2019Riedl et al , 2021. Another crucial ingredient is the wave's behaviour in strong (i.e., non-Wentzel-Kramers-Brillouin, non-WKB) stratification.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that these modes couple efficiently to Alfvén waves through resonant absorption (Hansen & Cally 2009;Cally & Andries 2010;Khomenko & Cally 2012). Currently, investigations are ongoing to what happens if the cross-field structuring is included into the wave propagation model (Cally & Khomenko 2019;Riedl et al 2019Riedl et al , 2021. Another crucial ingredient is the wave's behaviour in strong (i.e.…”
Section: Introductionmentioning
confidence: 99%